2010
DOI: 10.1007/s00125-010-1937-z
|View full text |Cite
|
Sign up to set email alerts
|

Metformin regulates the incretin receptor axis via a pathway dependent on peroxisome proliferator-activated receptor-α in mice

Abstract: Aims/hypothesis Metformin is widely used for the treatment of type 2 diabetes. Although it reduces hepatic glucose production, clinical studies show that metformin may reduce plasma dipeptidyl peptidase-4 activity and increase circulating levels of glucagon-like peptide 1 (GLP-1). We examined whether metformin exerts glucoregulatory actions via modulation of the incretin axis. Methods Metformin action was assessed in Glp1r

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
227
2
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 272 publications
(256 citation statements)
references
References 34 publications
13
227
2
6
Order By: Relevance
“…Additional studies will be required to determine whether metformin can increase incretin receptor expression in human beta cells and thereby bolster incretin action in a meaningful way. Although there are undoubtedly more details to unravel regarding the mechanisms of action of metformin, the work by Maida et al [10] extends previous findings to indicate that metformin can be regarded as an enhancer of GLP-1 secretion and possibly as a GLP-1 sensitiser, beyond its known biological functions (Fig. 1).…”
Section: Ampk Amp-activated Protein Kinase Dpp-4mentioning
confidence: 52%
See 4 more Smart Citations
“…Additional studies will be required to determine whether metformin can increase incretin receptor expression in human beta cells and thereby bolster incretin action in a meaningful way. Although there are undoubtedly more details to unravel regarding the mechanisms of action of metformin, the work by Maida et al [10] extends previous findings to indicate that metformin can be regarded as an enhancer of GLP-1 secretion and possibly as a GLP-1 sensitiser, beyond its known biological functions (Fig. 1).…”
Section: Ampk Amp-activated Protein Kinase Dpp-4mentioning
confidence: 52%
“…Yet, contrary to these findings, metformin does not directly inhibit DPP-4 activity in vitro [9,14,16]. Maida et al [10] also found that metformin at doses exhibiting GLP-1-increasing effects exerted no effect on plasma DPP-4 activity in mice. Furthermore, metformin increased plasma GLP-1 levels in rats genetically lacking DPP-4 [9].…”
Section: Ampk Amp-activated Protein Kinase Dpp-4mentioning
confidence: 87%
See 3 more Smart Citations